Study protocol for Adaptive ChemoTherapy for Ovarian cancer (ACTOv): a multicentre phase II randomised controlled trial to evaluate the efficacy of adaptive therapy (AT) with carboplatin, based on changes in CA125, in patients with relapsed platinum-sensitive high-grade serous or high-grade endometrioid ovarian cancer - Michelle Lockley; Kathy Robinson; Rowan Miller; Charlie Gourley; Nicholas Counsell; Iain Mcneish; Trevor Graham; Uma Anne Mukherjee; Helen Hockings; Apini Patel; Priya Narayanan; Katie Wilkinson; et al. (BMJ Open)
Introduction Adaptive ChemoTherapy for Ovarian cancer (ACTOv) is a phase II, multicentre, randomised controlled trial, evaluating an adaptive therapy (AT) regimen with carboplatin in women with relapsed, platinum-sensitive high-grade serous or high-grade endometrioid cancer of the ovary, fallopian tube and peritoneum whose disease has progressed at least 6 months after day 1 of the last cycle of platinum-based chemotherapy. AT is a novel, evolutionarily informed approach to cancer treatment, which aims to exploit intratumoral competition between drug-sensitive and drug-resistant tumour subpopulations by modulating drug dose according to a patient’s own response to the last round of treatment. ACTOv is the first clinical trial of AT in this disease setting.Methods and analysis 80 patients will be randomised 1:1 to standard therapy (control) or AT (investigational) arms. The starting and maximum carboplatin dose in both arms is area under the curve (AUC) ×5 according to absolute nuclear medicine glomerular filtration rate. The AT regimen will modify the carboplatin dose according to changes in the serum biomarker CA125, a proxy measure of total tumour burden. Patients will receive treatment intravenously every 21 days for a maximum of 6 and 12 cycles in the control and investigational arms, respectively. The primary endpoint is modified progression-free survival (investigator-assessed using RECIST 1.1 (Response Evaluation Criteria in Solid Cancers) compared with the baseline prerandomisation scan rather than the radiological nadir), clinical progression or death from any cause. Secondary endpoints will include acceptability, deliverability, compliance, toxicity, CA125, quality of life and overall survival. ACTOv is open to National Health Service hospitals throughout the UK, recruitment is anticipated to take 36 months across 10 sites and will be managed by the Cancer Research UK and University College London Cancer Trials Centre.Ethics and dissemination The trial has been reviewed and received approval from the London—Dulwich Research Ethics Committee (REC). Results of the trial will be disseminated through publication in peer-reviewed journals.Trial registration number NCT05080556.